A Spectacular Post-Starburst Quasar - Brotherton, MS; Breugel, W; Stanford, SA; Smith, R; Boyle, B; Miller, L; Shanks, T; Croom, S; Filippenko, A (Institute of Physics Publishing, 1999)
We report the discovery of a spectacular ``post-starburst quasar'' UN J1025-0040 (B=19; z=0.634). The optical spectrum is a chimera, displaying the broad Mg II emission line and strong blue continuum characteristic of quasars, but is dominated in the red by a large Balmer jump and prominent high-order Balmer absorption lines indicative of a substantial young stellar population at similar redshift. Stellar synthesis population models show that the stellar component is consistent with a 400 Myr old instantaneous starburst with a mass of less than or about 10^{11} solar masses. A deep, K_s-band image taken in 0.5 arcsec seeing shows a point source surrounded by asymmetric extended fuzz. Approximately 70% of the light is unresolved, the majority of which is expected to be emitted by the starburst. While starbursts and galaxy interactions have been previously associated with quasars, no quasar ever before has been seen with such an extremely luminous young stellar population.